Design of a New Washing Machine to Clean the Needle Bed of an Electronic Flat Knitting Machine - Celik, Nevin; Yolcular, Irfan; Kasap, Songul; Golen, Mehmet B.; Taskiran, Ali (Natl Inst Science Communication-Niscair, 2025)
An electronic flat knitting machine is traditionally used for knitting pullovers and other outerwear garments. When a typical electronic flat knitting machine runs for a certain time, the needle bed is filled with dust and lubrication. In order to solve this problem, a new needle bed cleaning machine is designed and manufactured by R&D department of NIT ORME Co. located in Turkey. In this article, the introduction of the washing machine, of which the prototype is produced and patented, and some analyzes, such as; structural, fluid flow and vibration, performed during the design of the machine is presented. SoloidWorks, ANSYS-Structural and ANSYS-CFX are the commercial softwares used for the analyses. As a result of the prototype production, the needle bed of knitting machines is automatically washed and dried faster than similar products in a practical, easier and functional way. Additionally, the cleaning costs are reduced by 70% with the washing machine.
Keywords: Design and prototype; Electronic flat knitting machine; Manufacturing; Needle bed washing; Optimization